Effectiveness of Treadmill Training Alone Versus Treadmill Training with External Clues on Improving Gait and Functional Ability in Parkinson’s Patient: Improving Gait and Functional Ability in Parkinson’s Patient - Ghafoor, Faisal; Fatima, Kanwal; Fawad, Muhammad; Munawar, Aisha; Baig, Muhammad Jawwad; Ahmad, Zunaira (Pakistan Journal of Health Sciences, 2023)
Parkinson's disease is a progressive neurological disease caused by degeneration of nerve cells in Substantia Nigra. It is characterized by postural instability, slowing of movement and tremor. Treadmill Training with Visual clues extensively used as an intervention to improve gait and Functional mobility. Objective: To compare the Treadmill training alone versus treadmill training with visual clues on improve gait and functional ability in Parkinson’s disease. Methods: It is assessor blind randomized controlled trial conducted in CMA Research and Teaching hospital, Lahore from 6th June 2022 to 6th January 2023.The sample size of 74 were divided into two groups. Group A received treadmill training session for 30 minutes while. The Group B received treadmill training with external clues like visual, auditory, etc. Each Participant received total 56 sessions for 28 weeks. The outcome measures was functional Activity measures with Wisconsin gait scale for Gait and Motor Aspects of Experiences of Daily Living (M-EDL) questionnaire. The Data were assessing at baseline by using these two scales. Results: The between groups comparison of post value showed that Group B showed a significant (<0.05) improvement in the (M-EDL) scale for the activities of daily living and significant (<0.05) improvement in the step length, stance width, hip hiking, pelvic rotation, external rotation, and toe clearance. Conclusions: It was concluded that the treadmill training with external clues is better as compared to the treadmill training alone for improving the gait and functional ability in the Parkinson patient.